Socialization of Land Kangkung (Jpomoea Reptans Poir) Cultivation in Cibungur Village, Tasikmalaya, Indonesia - Fahmi Sidiq (International Journal of Research in Community Services, 2021)
The cultivation technique of land kangkung (Ipomoea reptana Poir) which is practiced by farmers is a non-machine technique. Farmers' cultivation techniques are tillage, seed dispersal, fertilization and harvesting at 40 days after planting. The purpose of this study was to determine the internal and external factors that influence the development of organic kale farming, and to determine the appropriate development strategy for organic kale farming. Data collection methods used are interviews, observation and literature study. The results of this study indicate that the internal strength factor in the development of organic kale farming is the availability of adequate organic fertilizer, while the weakness is the weakness of the product produced cannot meet consumer needs and organic labels. The external factor is the opportunity for organic kale to be marketed online, while the threat is the sale of more and more non-organic vegetables at lower prices.